Percepções de Estudantes acerca de um Instrumento Diferenciado de Avaliação em Aulas de Matemática - Trevisan, André Luis; De Buriasco, Regina Luzia Corio [UNESP] (FapUNIFESP (SciELO), 2016)
This study describes the perception of high school students about the use of a different assessment tool in Mathematics classes: a test carried out in several phases. We tried to identify evidence of how they saw and judged this instrument (their perceptions) and identify possible implications of this use on the student's study strategies. The data were analyzed and collected through a questionnaire answered by the students at the end of the last stage of the test, as well as notes performed by them in their daily lessons. The reflections afforded from this analysis helped us understand the students themselves as subjects of the assessment process and allowed a critical analysis of the instrument as well as of the teacher's assessment practice.
Students perceptions about a differential assessment tool in mathematics classroom
Keywords: Assessment in School Mathematics; Mathematics Education; Stage Test; Students Perceptions